Artemisinin supplementation in concentrated cottonseed protein basal diets enhances growth, antioxidant capacity, intestinal immunity and microbiota in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Ling Pan; Qi Wang; Weikang Li; Xiaohui Dong; Shiwei Xie; Beiping Tan; Hongyu Liu; Yan Wang (Aquaculture Reports)
Artemisinin is a natural compound extracted from Artemisia annua, widely used in traditional Chinese medicine, with various bioactivities including antimalarial, anti-inflammatory, antioxidant, and immunomodulatory effects. In recent years, its potential in aquaculture has gained attention, but the physiological functions of its bioactive components in aquatic animal production remain underexplored and require further investigation. This study investigated the application of artemisinin in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) fed a diet in which Cottonseed protein concentrated (CPC) replaced 50 % of fishmeal protein. Hybrid grouper, with an initial weight of 7.83 ± 0.01 g, totaling 540 fish, were divided into six groups and fed different experimental diets over a period of 8 weeks. The groups included: 50 % fishmeal as a positive control (PC), 50 % fishmeal protein replaced by CPC as a negative control (NC), and artemisinin added at 0.40 %, 0.80 %, 1.20 %, and 1.60 % (T1–4). The results showed that hybrid grouper fed 0.40 % artemisinin exhibited a significant improvement in growth rate (P < 0.05). Additionally, the artemisinin-treated groups exhibited improved intestinal digestibility and mucosa health, as evidenced by increased α-amylase, lipase and trypsin activities, along with enhancements in villus height, villus width, and muscle thickness (P < 0.05). In the artemisinin-treated groups, significant alterations in gene expression were observed, including a marked upregulation of interleukin-8, tumor necrosis factor-α, and toll-like receptor-2 (P < 0.05); however, the expression of tumor necrosis factor-β and toll-like receptor-1 was significantly downregulated (P < 0.05), suggesting that artemisinin may mitigate intestinal inflammatory injury. Artemisinin supplementation significantly enhanced the activities of SOD, GSH-Px, CAT, and T-AOC in the liver and hindgut (P < 0.05),while also reducing MDA levels, thereby demonstrating its protective effect against oxidative stress and its ability to strengthen antioxidant defense system. Microbiome analysis demonstrated that artemisinin decreased microbial diversity and richness while selectively promoting the proliferation of beneficial gut microbiota, suppressing harmful bacteria, and enhancing the intestinal environment, thereby supporting overall growth. In summary, artemisinin enhanced mucosal morphology and digestive enzyme activity, thereby elevating the apparent metabolic rate and promoting growth in grouper. Furthermore, it conferred notable advantages related to antioxidant activity, immune modulation, and intestinal health. Broken-line regression analysis based on the WGR indicated that the optimal dietary artemisinin level was estimated to be 0.40 %.